Prevention of second-hand smoke exposure among pregnant women and children in Egypt and the rest of the Middle East: a mixed-methods investigation - Hassanein, Zeinab M. (2023)
Second-hand smoke (SHS) exposure is a major public health concern. Pregnant women and children are a priority population for tobacco control efforts because second-hand smoke (SHS) exposure during pregnancy/childhood poses serious risks to foetal/child health. Due to strong cultural constraints against women smoking in many Middle Eastern countries, the prevalence of tobacco smoking is higher among men than women, which puts non-smoking women and children on risk of exposure to SHS. The Middle Eastern countries are Bahrain, Cyprus, Egypt, Iran, Iraq, Israel, Jordan, Kuwait, Lebanon, Oman, Palestine, Qatar, Saudi Arabia, Syria, Turkey, United Arab Emirates, and Yemen.